Ukraine after Maidan : revisiting domestic and regional security - Stępniewski, Tomasz; Soroka, George (Soviet and post-Soviet politics and society ;, 2018)
When public protests first began in Ukraine at the end of 2013, the failed promise of the Orange Revolution was still fresh in the minds of many Ukrainians. However, unlike in the aftermath of 2004-2005, the political and military crises ignited by the Euromaidan brought profound changes not only for Ukraine, but also for neighboring states and Europe more generally, calling into question the durability of the post-Cold War world order. Writing from a variety of viewpoints and backgrounds, this volume's contributors offer sustained analysis of how its legacies have reverberated throughout the postcommunist region and wider Europe.